Analysis of the policy and process of voter registration in South Africa in the 1999 general elections - Mlitwa, Nhlanhla Boyfriend Wilton (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Phil.)--Stellenbosch University, 2000.